Integration of gamification into the andragogical process of the physics area for intensive evening high school students - Pinos-Maldonado, Diana (2026)
This research analyzes the low academic performance, lack of motivation, and limited participation of adult and senior citizens with incomplete schooling in the Physics course within the intensive evening high school program. This problem is crucial, as it affects a traditionally excluded group whose education is vital for their personal and social development. Classical teaching strategies have proven insufficient to achieve meaningful learning and active participation in this andragogical context. The central proposal consists of incorporating gamification into the teaching process, based on the characteristics of adult learning. To make the teaching of complex concepts, such as density, dynamic game elements and specific digital platforms (Websim and Spatial) were used. The methodology employed is a mixed-methods approach, based on the Sequential Exploratory Design (DEXPLOS) model, integrating qualitative analysis (interviews and observation sheets) and quantitative analysis (satisfaction surveys). The study was conducted with students and educators in the intensive evening program in the city of Azogues, Ecuador. Among the main results, a significant improvement was observed in motivation, conceptual understanding, active participation in the classroom, collaborative work, and the development of critical thinking. Contextualized and accessible gamification proved capable of transforming the teaching and learning process, fostering meaningful and resilient knowledge. This proposal represents an inclusive and replicable alternative for optimizing the teaching of Physics in vulnerable contexts.